Factors Affecting the Outcomes of COVID-19 Patients Treated at Dr. M. Djamil Padang General Hospital - Yessy Susanty Sabri; Dewi Wahyu Fitrina; M. Hari Nandi Pinto; Lusi Agustini Arda; Nova Indriyani; Kornelis Aribowo; Ilham Ilham; Dimas Bayu Firdaus (Jurnal Respirologi Indonesia, 2022)
Background: COVID-19 has spread rapidly throughout the world with high morbidity and mortality. This study aimed to determine the factors that influenced the outcomes of COVID-19 patients treated at RSUP. Dr. M. Djamil Padang.Methods: This was an observational analytic study conducted with a retrospective cohort design on COVID-19 patients at RSUP Dr. M. Djamil Padang. Data were taken from medical records from January to March 2021. Association between comorbidities and the outcome of COVID-19 patients were analyzed using Chi- Square/Fisher Exact Test.Results: Majority of the patients were female (56.4%) and aged above 50 years (64.3%). Hypertension was the most common comorbidity (41.1%). Diabetes mellitus affected the final outcome of treatment. The number of comorbidities the patients had was associated with a worse outcome for COVID-19.Conclusion: Most of COVID-19 patients at RSUP Dr. M. Djamil Padang were male and more than 50 years old. There was a correlation between age, gender, and comorbidities in COVID-19 patients with the outcomes.